2023
DOI: 10.3390/su15032165
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Attenuation and Mechanical Characteristics of a Lead/NBR/SBR Rubber Composite with Black Nanocarbon Reinforcement

Abstract: In this work, black nanocarbon-loaded 0–100 parts-per-hundred (phr) PbO-filled acrylonitrile butadiene rubber (NBR)/styrene-butadiene rubber (SBR) blend composites were prepared by using an ordinary standard rubber mixer. Both mechanical and gamma attenuation properties of the prepared samples were investigated. Maximum tensile strength and elongation at break were obtained at 40 phr PbO concentration. The obtained values for the mass attenuation coefficient with the increased PbO concentration from 0–100 phr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The planes (101) and ( 211) are related to TiO 2 [44]. In addition, the average crystalline size and crystallinity were 35.4 nm and 38.43%; these results agree with previous studies [32,45]. Adding zinc oxide and titanium oxide leads to a complex structure with the rubber and enhances the rubber's crystalline properties [46].…”
Section: Xrd Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…The planes (101) and ( 211) are related to TiO 2 [44]. In addition, the average crystalline size and crystallinity were 35.4 nm and 38.43%; these results agree with previous studies [32,45]. Adding zinc oxide and titanium oxide leads to a complex structure with the rubber and enhances the rubber's crystalline properties [46].…”
Section: Xrd Analysissupporting
confidence: 87%
“…Figure 3 shows the FTIR spectra of pure SBR and SBR: Pb -NPs with a range of 500-4000 cm − 1 ; the peaks around 2924 and 2846 cm − 1 represent the symmetric stretching of the C-H band [32,[37][38][39]. The The peaks observed at 802 cm − 1 and 887 cm − 1 correspond to the C = C bending attributed to the alkane group.…”
Section: Ftir Analysismentioning
confidence: 99%
“…The HVL was estimated in this study to analyze the penetrating ability of gamma radiation through PbO NSs grown on a glass layer under different temperatures 50 and 70 °C, and it reduces with an increase of μ. As shown in Table , the lead-oxide NSs have highly efficient rate of performance for protection from the radiation, and the obtained results are better than those from previous studies. , …”
Section: Resultsmentioning
confidence: 69%
“…As shown in Table 2, the lead-oxide NSs have highly efficient rate of performance for protection from the radiation, and the obtained results are better than those from previous studies. 46,47 The SEM images in Figure 4 revealed that the PbO sample grown at 50 °C has a more and clear grain boundary structure compared to the PbO sample synthesized at 70 °C. In addition, the crystal quality of 50 °C samples is higher than the other one; see Figure 3.…”
Section: Hvl Ln 2 =mentioning
confidence: 99%
See 1 more Smart Citation